An Advanced Reading Course in Japanese with Wikipedia: A Case Study - Yoko Hasegawa; Kiyono Fujinaga-Gordon; Jun Kanazawa; Eri Nakagawa (Japanese Language and Literature, 2023)
This paper proposes integrating the activity of Wikipedia-article authoring into an advanced-level Japanese reading course. With its unprecedented wealth of information and unique feature of collaborative writing, Wikipedia has been recognized as a powerful pedagogical tool. Nevertheless, adapting it to a course requires a considerable amount of planning and preparation. Probably because of this high threshold, it is yet to be widely employed by L2 educators. In the fall of 2022, we experimentally taught a course, assigning short Japanese Wikipedia articles for translation into English. This paper provides information sufficient for those interested in experimenting with this potential resource to enhance their courses.